The Role of social media in developing new meaning in Arabic language - Miftakhul Jannah, Dias Ayu; Halimah, Siti Nor; Hasaniyah, Nur (Abjadia : International Journal of Education, 2025)
The development of information and communication technology, especially through social media such as Twitter, Instagram, TikTok, and Facebook, has brought significant influence on the Arabic language. This study aims to examine the role of social media in generating new meanings in Arabic through linguistic phenomena such as neologisms, word meaning changes, as well as the use of creative local dialects. Using a descriptive-analytical qualitative approach, data is collected from new terms that appear on social media and supported by related academic literature. The results showed that social media became an important medium in the birth of new vocabulary such as hashtag, influencer, and selfie, as well as meaning changes in traditional words such as viral and visually appealing. This phenomenon reflects the linguistic creativity of the younger generation, the influence of globalization, and the dynamics of Arabic language adaptation to digital culture. However, the massive influx of foreign terms also poses a challenge to the preservation of classical Arabic. This study confirms that social media acts as a major agent in the evolution of contemporary Arabic.